Screening effects caused by electron-electron interactions in crystaline structures with intermediate dimensionality - Tovstyuk, N.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
In the paper studied are polarization properties of an electron subsystem in the structures of intermediate dimension, particularly, in the quasi-two-dimensional structures depending on the degree of quasi-two-dimensionality. These investigations were founded on the model dispersion law that most completely governs the peculiarities of the structure. Here, we studied the character of alternating oscillations of the potential screened by interelectron interaction, namely, by its anisotropy depending on microscopic parameters that determine the shape of isoenergetic surface and the degree of quasi-two-dimensionality. It is shown that the obtained potential, in comparison with similar results for isotropic Fermi gas, oscillates at smaller distances with amplitude of an order of magnitude higher and with a period of an order of that smaller.